2021
DOI: 10.1007/s10147-021-02085-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nivolumab combined with brentuximab vedotin after nivolumab monotherapy failure in patients with relapsed and refractory classic Hodgkin lymphoma

Abstract: Objectives Therapy of patients with relapsed and refractory classic Hodgkin lymphoma (r/r cHL) after PD-1 inhibitors failure remains an unresolved issue. The aim of this study was to evaluate the efficacy and safety of the combination of nivolumab with brentuximab vedotin (Nivo + BV) after nivolumab monotherapy failure. Methods This study retrospectively analyzed 21 patients with r/r cHL who were treated with the combination of Nivo + BV after Nivo failure. The response was evaluated by PET-CT scan according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In the CheckMate 205 study, nivolumab showed efficacy in patients with R/R cHL who had previously been treated with BV, 10 and a retrospective analysis of patients with R/R cHL treated with nivolumab plus BV indicated promising efficacy. 30 R/R PMBL shares clinical and molecular features with R/R cHL, including high mutational density and expression of CD30, 13 , 14 , 15 , 31 and data reported here for CheckMate 436 possibly indicate a similar synergy in patients with R/R PMBL.…”
Section: Discussionsupporting
confidence: 55%
“…In the CheckMate 205 study, nivolumab showed efficacy in patients with R/R cHL who had previously been treated with BV, 10 and a retrospective analysis of patients with R/R cHL treated with nivolumab plus BV indicated promising efficacy. 30 R/R PMBL shares clinical and molecular features with R/R cHL, including high mutational density and expression of CD30, 13 , 14 , 15 , 31 and data reported here for CheckMate 436 possibly indicate a similar synergy in patients with R/R PMBL.…”
Section: Discussionsupporting
confidence: 55%
“…While 90% of the patients with HL can be cured by standard first-line treatment, 10%–30% of patients show relapse or refractory disease after the standard first-line treatment. 4 , 7 Younger patients tend to be healthier, and therefore, can often tolerate higher-intensity chemotherapy and AHCT. Thus, AHCT was reported to afford a better prognosis and adopted as the standard treatment for R/R patients, according to the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Brentuximab vedotin (BV) and immune checkpoint inhibitors (ICIs) have revolutionized the treatment paradigm for patients with refractory or relapsed (R/R) disease, resulting in response rates higher than 50%. 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 These new agents have been subsequently included in earlier lines of therapy, including pre-AHCT salvage, post-AHCT consolidation, and first-line treatments. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 This change in practice means that patients with single- or double-refractory (refractory to BV and/or ICIs) disease are becoming a common clinical problem.…”
Section: Introductionmentioning
confidence: 99%
“…BV has produced promising results even when given as a single agent in the treatment of R/R cHL (overall response rates [ORR], 57%-75% alone or with nivolumab 11 , 12 , 13 , 14 , 15 ), R/R CD30+ non-Hodgkin lymphomas (ORR, 36%-44%; complete response rate [CRR], 17%-24%), 4 , 5 and R/R ALCL (ORR, 67%-86%; CRR, 56%-66%). 12 , 16 Although designed to target CD30, the efficacy of BV has also been shown in lymphomas with variable 5 , 6 or absent 17 , 18 CD30 expression, such as non-Hodgkin B-cell lymphoma or non-ALCL T-cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%